2ME2 increase radiation‐induced apoptosis of keloid fibroblasts by targeting HIF‐1α in vitro. (15th April 2015) - Long, Fei; Si, Loubin; Long, Xiao; Yang, Bob; Wang, Xiaojun; Zhang, Fuquan
Abstract: Background: Radiation therapy is considered to be a treatment for keloid scarring; however, radioresistance has been shown to be a serious impediment to treatment efficacy. There is therefore a need for the discovery of novel critical molecular targets whose inhibition might enhance the radiotherapeutic response. An elevated level of hypoxia inducible factor (HIF)‐1α expression after radiation therapy in keloid fibroblasts has been demonstrated in our recent experiments. Therefore, we suggested there was a possible close relationship between HIF‐1α and keloid radioresistance. The current study aimed to investigate whether target HIF‐1α may enhance the radiotherapeutic efficacy of keloids. Methods: 2‐methoxyestradiol (2ME2) was applied to inhibit HIF‐1α expression, and the treatment results were assessed by cell proliferation, apoptosis and radiosensitivity. A lentivirus‐mediated small interfering RNA (siRNA) transduction method was used to block the expression of HIF‐1α gene. Results: Both mRNA and protein levels can be effectively inhibited after the knockdown of HIF‐1α, leading to a significant increase of radiation‐induced apoptosis in keloid fibroblasts. Our experiment also demonstrated that 2ME2 could effectively inhibit the protein expression of HIF‐1α, which significantly increased the late stage of radiation‐induced apoptosis of keloid fibroblasts. Conclusions: The present study indicates that HIF‐1α might serve as a therapeutic target for keloids. Furthermore, suppression of HIF‐1α by 2ME2 may be a promising therapeutic adjuvant in radiation therapy for keloids.